Real-world efficacy and safety of nebivolol in Korean patients with hypertension from the BENEFIT KOREA study. Issue 3 (March 2020) - Shin, Jinho; Choi, Yu Jeong; Hong, Geu-Ru; Jeon, Dong Woon; Kim, Dae-Hyeok; Koh, Young Youp; Mancia, Giuseppe; Manolis, Athanasios J.; Yoon, Hyuck-Jun; Park, Sang Won
Abstract : Objective: The efficacy and safety of nebivolol in patients with hypertension is well established, but its effect in Asian patients with essential hypertension in the real world has not been studied. Methods: Adult South Korean patients with essential hypertension, with or without comorbidities, were enrolled to participate in this prospective, single-arm, open, observational study; 3011 patients received nebivolol either as monotherapy or add-on therapy. Changes in SBP, DBP and heart rate (HR) at 12 and 24 weeks were evaluated. Subgroup analysis for BP changes in newly diagnosed (de novo) patients and those receiving other antihypertensives at study entry were also conducted. Results: Nebivolol significantly decreased mean SBP and DBP at 12 and 24 weeks compared with baseline ( P < 0.0001). A significant reduction in HR was also observed at 12 and 24 weeks ( P < 0.0001). The reductions of SBP and DBP were notably greater when nebivolol was used as monotherapy in de novo patients ( P < 0.0001) and as add-on therapy to existing antihypertensives (angiotensin II receptor blockers, angiotensin-converting enzyme inhibitors and calcium channel blockers; P < 0.0001). Majority of the reported adverse events were mild; the most common adverse events were dizziness (1.3%), headache (1.0%) and dyspnea (0.9%). Conclusion: Despite the limitations associated with observational studies, this real-world study in Asian patients with essential hypertension with and without comorbidities, demonstrated the efficacy and safety of once daily nebivolol, either as monotherapy or add-on therapy. Clinical trial registration number: NCT 03847350. SDC Callout: Video Abstract, http://links.lww.com/HJH/B172 Abstract : Supplemental Digital Content is available in the text